PENGARUH CARDIO DANCE TERHADAP PENURUNAN TINGKAT STRES PADA WANITA PREMENOPAUSE - Sari, Reno Siska; Mardikaningsih, Agusti; Kurniasari, Praharisti; Zaini, Moh (Journal of Physical Activity and Sports (JPAS), 2025)
The premenopausal phase is a transitional period characterized by irregular ovulation and menstrual cycles. During this phase, hormonal changes, decreased reproductive function, physical changes, and psychological disorders occur. Stress is a psychological disorder that often occurs in the premenopausal phase and, if left untreated, will impact chronic and mental health. One effort to overcome stress levels in premenopausal women is cardio dance. This study aims to determine the effect of cardio dance training on reducing stress levels in premenopausal women at the Annisa Regency Housing Complex in Malang City. This study was a pre-experimental study with a one-group pre-post test design. The sample used was 18 people with a purposive sampling technique. Data collection used questionnaires before and after treatment. Data analysis was performed using a paired t-test. The average stress level before cardio dance training was 16.61 with a standard deviation of 1.71. The average stress level after cardio dance training was 12.22 with a standard deviation of 1.86. The results of the analysis showed that cardio dance had an effect on reducing stress levels with a p value of 0.000 (<0.05).